CFD – facilitated prognosis of bubble bed bioreactor performance based on bubble swarms oscillation analysis - Vlaev, S. D. (Array, 2009)
Summary: Bubble column reactors are widely used as gas-liquid and gas liquid-solid contactors in biotechnology applications. A basic issue in biotechnology is oxygen availability related to gas hold-up distribution, since aerobic bioprocessing depends on the dissolved oxygen substrate. The aim of this study is to analyze oxygen availability in bubble column bioreactors in terms of specific spatial and temporal gas-liquid flow. 3D CFD simulation is used to simulate the dispersed gas-liquid flow field of a bubble column of ID 0.29 m equipped with metal distributing plate. The solution is based on the Euler/Euler approach, the standard k-ε model, and the standard wall function treatment. A single size particle model was employed. No mass transfer between the gas and the liquid phase was studied; oxygen transfer is discussed in terms of local and temporal gas hold-up distribution. Two cases of different viscosity are studied related to water-like and sugar-containing nutrient media cases, e.g. tap water and aqueous solution of 0.3 kg kg–1 saccharose, respectively. Conditions of oxygen availability for aerobic cell growth in a bio-fluid at condition of elevated viscosity are considered. The time-course of instantaneous oxygen delivery proportional to the dispersion capacity estimated as gas hold-up is uncovered. The results are presented in the form of contour plots and radial profiles of the local gas hold-up at different bed height positions. The oscillating behaviour of the gas hold-up is illustrated and summarized into oxygen availability plot related to position. Based on the CFD analysis, clues for rational bioprocess performance time-course could be inferred